A review on sustainable urban vehicle routing. (20th February 2021) - Dündar, Hasan; Ömürgönülşen, Mine; Soysal, Mehmet
Abstract: The challenges of simultaneous profit maximization and environmental or social externality mitigation need to be urgently addressed by companies. Accordingly, attention to the Sustainable Vehicle Routing Problem incorporating economic, environmental, and social concerns has been gradually increasing. To the best of our knowledge, this is the first literature review that focuses on sustainability practices in urban routing. Our first objective is to investigate the scopes, objectives, solution methodologies, and data types in the reviewed papers. The second objective is to analyse the indicators used in the proposed quantitative models and how they are related to sustainability and green criteria in the vehicle routing field. These criteria are adapted from Elkington's (2001) triple bottom line (TBL) approach that emphasizes economic, environmental, and social dimensions. The final objective is to examine the findings of the studies, identify gaps in the related literature, and suggest directions for future research. One of the key findings of this study is that the economic dimension is the prominent driver among the three pillars of sustainability. The researchers relatively less address the environmental and social dimensions. It is determined that the social indicators are the least studied sub-dimension of sustainability. The results of this study are thought to help researchers and practitioners to learn more about the methods and models of sustainability or green practices, the metrics used, and the economic, environmental, and social results. Highlights: The reviewed papers were classified according to Elkington's TBL approach. The dimensions of sustainability, economic, environmental and social, were deeply examined. The managerial insights into urban logistics designs were highlighted. The confusion on the key performance indicators was clarified. The gaps in the sustainable urban vehicle routing were indicated.